The Impact of the Quality of Care for Adults with Acute Asthma in the Emergency Department of a Tertiary Hospital: A 1-Year Follow-Up Study - Carlos Martinez Rivera; Agnes Hernandez Biette; Anna Núñez Condominas; Ignasi Garcia Olive; María Basagaña Torrentó; Clara Padró Casas; Leandro Tapia Barredo; Antoni Rosell Gratacós (Clinics and Practice)
Background/Objectives: This study evaluates the adherence to guidelines for the management of asthma exacerbations in the ED, recommendations at discharge, and impact at a 1-year of follow-up. Methods: An observational study of 87 asthma patients who attended the ED during 2022 and were discharged within 24 h was carried out. Data before the ED admission, care in the ED, and discharge reports, as well as the clinical characteristics at follow-up, were recorded. The relationship between complete ED discharge reports and outcome at 1 year, and factors associated with new exacerbations were analyzed. Results: The mean age was 51 years, 80% of the patients were women, and 50% had severe asthma. Prior to ED admission, 58.8% of patients used ICS-LABA, 26.2% triple therapy, 31.8% had not been treated, and 51.2% had presented at least one exacerbation. On ED admission, PEF was measured in 21% of patients only, decreasing to 6.8% at 3 h. In the ED discharge reports, the use of systemic corticosteroids was recommended in 76.5% of the cases and ICS-LABA in 46.9%. However, complete ED discharge reports were recorded for only 18.2% of patients. A total of 6.7% of patients were referred to a primary care physician and 29.9% to a pneumologist. Complete ED discharge forms did not improve asthma control at follow-up or reduce new exacerbations. Exacerbations before ED admission (OR 2.49, 95% CI 1.47–4.22, p = 0.001) and the use of any asthma controller treatment (OR 1.84, 95% CI 1.84–507, p = 0.017) were associated with ≥2 exacerbations at follow-up. Conclusions: Contact with ED did not improve disease control or reduce exacerbations. It is necessary to optimize care before, during, and after exacerbations by developing integrated programs with primary care to improve asthma management.